Alignment options and robotics in total knee arthroplasty - Aflatooni, Justin O.; Wininger, Austin E.; Park, Kwan J.; Incavo, Stephen J. (Frontiers in Surgery, 2023)
Total knee arthroplasty is one of the most widely performed surgical procedures today. Its widespread popularity has helped drive innovation and improvement in the field. Different schools of thought have developed regarding the best way to perform this operation. Specifically, there are controversaries regarding the best alignment philosophy for the femoral and tibial components to optimize implant stability and longevity. Traditionally, neutral mechanical alignment has been the preferred alignment target. More recently, some surgeons advocate for alignment matching the patient’s pre-arthritic anatomic alignment (“physiologic” varus or valgus), which has been described as kinematic alignment. Functional alignment is a hybrid technique that focuses on the coronal plane minimizing soft tissue releases. To date, there is no evidence demonstrating superiority of one method over another. There is growing popularity of robotic surgical techniques to improve accuracy of implant position and alignment. The choice of alignment philosophy is an important aspect of robotic assisted TKA surgery and has the potential to clarify the optimal alignment technique.